Pengaruh Kepuasan, Motivasi Dan Disiplin Kerja Terhadap Kinerja Pegawai Pada Sekretariat Auditorat Keuangannegara Badan Pemeriksa Keuangan Republik Indonesia - Huda, Nurul; Komalawati, Euis (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
This research is motivated by the decline in employee performance which is influenced by several factors that will be tested in this research. This research aims to analyze the influence of job satisfaction, motivation and work discipline on employee performance at the Secretariat of the State Financial Auditor of the Republic of Indonesia Financial Audit Agency. This research uses a quantitative method with a survey approach, where data is collected through questionnaires distributed to 227 employees within the Secretariat of the State Financial Auditor. The data analysis technique used is multiple linear regression to determine the influence of each independent variable on the dependent variable. The results of the research show that the variables job satisfaction (X1), motivation (X2), and work discipline (X3) are able to explain the employee performance variable (Y) by 94.1% while the remaining 5.9% is explained by other variables not included in the model. Job satisfaction has a strong positive influence, showing that employees who are satisfied with their work tend to have better performance. Motivation also has a significant effect, where motivated employees have high work enthusiasm and productivity. Work discipline was found to be an important factor that supports optimal performance, with employees who have high discipline tending to be more efficient and effective in carrying out their duties. The implications of this research indicate that to improve employee performance, management needs to focus on increasing job satisfaction, providing the right motivation, and enforcing consistent work discipline. The recommendation for the Supreme Audit Agency is to implement programs that can increase job satisfaction, such as rewards and recognition, as well as providing training and development that can increase employee motivation and work discipline.